Two new Stenaelurillus species (Araneae, Salticidae, Aelurillina) from Western Ghats, India - Puthoor Pattammal Sudhin; Souvik Sen; John T. D. Caleb (Zoosystematics and Evolution, 2023)
Two new species – Stenaelurillus megamalai sp. nov. (♂♀) from the colorful group and Stenaelurillus neyyar sp. nov. (♂♀) from the black and white group – are described from the southern Western Ghats of India. Detailed morphological descriptions, illustrations, as well as the distribution maps are provided. New distributional data for three other species, Stenaelurillus albus Sebastian, Sankaran, Malamel & Joseph, 2015, S. arambagensis (Biswas & Biswas, 1992) and S. wandae Logunov, 2020 are also provided.